Analisis Strategi Treasury Single Account dalam Meningkatkan Efisiensi dan Efektifitas Pengelolaan Kas Umum Daerah - Isti'anah - (ILTIZAM Journal of Shariah Economics Research, 2022)
The Indonesian government has developed a Treasury Single Account (TSA) as a form of Public Financial Management reform since the last decade and a half. Despite its impressive success where previously idle cash balances in commercial banks, its have been consolidated into government accounts at Bank Indonesia (BI). T he development of the TSA is not yet complete. This paper investigates the TSA has been developed in Indonesia and identifies the gap between international best practice. The current literatures on TSA used to observe the existing TSA policies in Indonesia. Based on the analysis of the literatures, this study found that there is still a gap between the achievements and some significant things. The veracity of some of the literatures that has proven successful is worth considering. I n addition to ensuring that the development of the current TSA has been carried out properly. This study is expected to contribute to the development of the current TSA in Indonesia by providing recommendations regarding the overall implementation of Virtual Accounts for all public fund accounts, the continuous development of all TSA supporting components, as well as the adoption of other countries' success by adjusting the specific conditions of Indonesia